Strategi penetrasi pasar UMKM Kota Semarang menghadapi era pasar global MEA - Cicik Harini; Yulianeu Yulianeu (Jurnal Ekonomi dan Bisnis, 2018)
Competition among small, micro and medium-sized businesses continues to increase, therefore efforts are needed so that SMEs are able to maintain the sustainability of their businesses in facing the global market era of the ASEAN Economic Community. The effort is to improve the smallest strategy to bear the risk of failure known as the market penetration strategy. The population of the study was UMKM in Semarang City, with a total sample of 120 respondents determined through purposive sampling technique. The method in this research using Structural Equation Modelling-Partial Least Square analysis method. The findings of the study indicate that market penetration has a positive influence on the marketing mix and marketing performance and the direct influence of market penetration is greater on marketing performance than the effect mediated by the marketing mix. Therefore, the strategy of market penetration can be increased through increasing customer sustainability, increasing sales in existing markets, increasing value, increasing existing market share, and increasing the existing market size.